2017
DOI: 10.1515/fhort-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physiological responses of grapevine (Vitis vinifera L.) to drought stress and dust pollution

Abstract: Dust pollution can negatively affect plant productivity in hot, dry areas with high insolation during summer. To understand the effect of water-deficit and its interaction with dust pollution on vegetative and physiological changes in grapevine ʻBidaneh Sefidʼ, two-year-old plants were subjected to drought stress (-0.1 and -1 MPa) and dust treatment in a greenhouse during 2013 and 2014. The results showed that dust had a significant negative effect on the number of leaves, shoot length, root and shoot dry weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
(42 reference statements)
3
12
0
Order By: Relevance
“…Diminution of root growth under water stress has been related to the loss of cell turgor and increased penetration resistance of dried soils ( Bengough et al, 2011 ). In addition, a recent study suggested that the loss of leaves could decrease the supply of carbohydrates and/or growth hormones to meristematic regions, thereby inhibiting growth ( Karami et al, 2017 ). In accordance with previous studies, severe water deficits led to lower shoot to root ratio because root growth is generally less affected than shoot growth in drought-stressed grapevines ( Karami et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diminution of root growth under water stress has been related to the loss of cell turgor and increased penetration resistance of dried soils ( Bengough et al, 2011 ). In addition, a recent study suggested that the loss of leaves could decrease the supply of carbohydrates and/or growth hormones to meristematic regions, thereby inhibiting growth ( Karami et al, 2017 ). In accordance with previous studies, severe water deficits led to lower shoot to root ratio because root growth is generally less affected than shoot growth in drought-stressed grapevines ( Karami et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study suggested that the loss of leaves could decrease the supply of carbohydrates and/or growth hormones to meristematic regions, thereby inhibiting growth ( Karami et al, 2017 ). In accordance with previous studies, severe water deficits led to lower shoot to root ratio because root growth is generally less affected than shoot growth in drought-stressed grapevines ( Karami et al, 2017 ). Given that grapevine vegetative growth occurs soon after bud break in springtime, our results corroborated the crucial role of water availability during that period on vine development, physiological performance, and yield components reported in previous studies ( Munitz et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The leaf is an important organ that consumes water, and its changes under different water supply conditions show the importance of maintaining the water balance in plants [28]. These phenomena are broadly reported, and acutely described in studies on grapevine [29] and wheat [30]. Therefore, P. ostii may reduce leaf water dispersion loss by reducing the light-receiving area or the early leaf fall time, so as to resist the drought.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, dust resulted in a significant decrease in yield and yield components of soybean compared with the control. Previous studies have shown that dust pollution resulted in a yield loss in cotton (Abdullaev & Sokolik, 2020), potato (Tomar et al, 2018), black gram (Phaseolus mungo L.) (Babu et al, 2018), rice (Sett, 2017;Sharma & Kumar, 2016), and grapevine (Karami et al, 2017). Hatami et al (2018) studied the effects of desert dust on yield and yield components of cowpea and found that exposure to desert dust significantly decreased biological yield and seed yield of cowpea by 28.3 % and 25.6 %, respectively, compared with normal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…; Calotropis procera R. Br. (Sarkar et al, 1986), and grapevine (Vitis vinifera L.) (Karami et al, 2017).…”
Section: Discussionmentioning
confidence: 99%